Patients satisfaction with health care services after cardiac surgery with artificial blood circulation - Sijūnienė, Agnė; Švagždienė, Milda (Slauga. Mokslas ir praktika, 2020)
The aim of modern healthcare is to pay as much attention as possible to the patient and his satisfaction with the healthcare services provided. Information about patient‘s experience is recognized and widely used measure of quality of service. A key aspect of improving the quality of anesthesia is the assessment of patient‘s satisfaction with anesthesia, which is influenced by the preoperative visit of the anesthesiologist, the type of anesthesia, and postoperative symptoms and pain management. The role of premedication in patient satisfaction with anesthesia is analyzed in this article. The quantitative study was performed in November-December, 2019 – in the Department of Cardiac Surgery at Lithuanian University of Health Sciences Hospital Kaunas Clinics in order to determine the influence of premedication on patient satisfaction with anesthesia after cardiac surgery with artificial blood circulation. Our results show that patients were generally satisfied with pain management and patient-anesthesiologist communication. The satisfaction with anesthesia was influenced by patient‘s education, age, and gender. The most common side effects during the first three postoperative days were sleeping problems and complicated speaking. Patients who received Midazolam preoperatively felt calmer before the surgery, compared to patients who did not receive Midazolam (p < 0.05). Additionally, patients who received pre-operative Midazolam had lower incidence of side effects during the first three days after surgery and higher satisfaction with anesthesia.